2022
DOI: 10.3390/cancers14030592
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and Prognostic Role of Pre-Therapy and Interim 68Ga-DOTATOC PET/CT Parameters in Metastatic Advanced Neuroendocrine Tumor Patients Treated with PRRT

Abstract: Peptide receptor radionuclide therapy (PRRT) is an effective therapeutic option in patients with metastatic neuroendocrine tumor (NET). However, PRRT fails in about 15–30% of cases. Identification of biomarkers predicting the response to PRRT is essential for treatment tailoring. We aimed to evaluate the predictive and prognostic role of semiquantitative and volumetric parameters obtained from the 68Ga-DOTATOC PET/CT before therapy (bPET) and after two cycles of PRRT (iPET). A total of 46 patients were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
(36 reference statements)
1
10
0
Order By: Relevance
“…This finding highlights that [ 68 Ga]Ga-DOTATOC PET/CT could also be important in the assessment of response to PRRT, which is actually performed only with RECIST 1.1 criteria on ceCT. Moreover, our study strengthens the results of Durmo and colleagues [26], highlighting the importance of a volumetric evaluation of the disease burden in patients treated with PRRT, both at baseline and at follow-up [ 68 Ga]Ga-DOTATOC PET/CT.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This finding highlights that [ 68 Ga]Ga-DOTATOC PET/CT could also be important in the assessment of response to PRRT, which is actually performed only with RECIST 1.1 criteria on ceCT. Moreover, our study strengthens the results of Durmo and colleagues [26], highlighting the importance of a volumetric evaluation of the disease burden in patients treated with PRRT, both at baseline and at follow-up [ 68 Ga]Ga-DOTATOC PET/CT.…”
Section: Discussionsupporting
confidence: 87%
“…Ezzidin et al [38] already reported a correlation between baseline liver tumor burden ≥25% on radiological imaging and OS after PRRT. Furthermore, Durmo et al [26] recently discriminated PRRT-responders from nonresponders according to baseline SRETV (which they called bTV), similarly to the work previously published by Pauwels et al [25]. To the best of our knowledge, this is the first work reporting that post-SRETV_WB and post-SRETV_L on [ 68 Ga]Ga-DOTATOC PET/CT both correlated with early clinical response.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…However, several approaches (i.e., CT-based, SUV-based, etc.) have been proposed for segmentation [ 51 , 52 ]; in particular, a threshold above 41% of SUVmax has been utilized for volume segmentation in neuroendocrine tumors [ 53 ]. In this regard, Kowalski and collaborators [ 33 ] applied a threshold of 2.3 SUVmax for contouring meningiomas’ lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Although peptide receptor radionuclide therapy (PRRT) is an effective therapeutic option in patients with metastatic NET, this treatment modality is inefficacious in about 15–30% of cases. The paper by Durmo et al [ 6 ] was designed to retrospectively identify biomarkers able to predict responses to PRRT in metastatic NET patients with different primary malignancies. The results found that a high baseline tumor volume was the only parameter negatively associated with the disease response to PRRT and patient survival.…”
mentioning
confidence: 99%